2018
DOI: 10.1186/s12901-018-0056-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and antimicrobial drug susceptibility pattern of bacterial pathogens from pediatric patients with otitis media in selected health institutions, Addis Ababa, Ethiopia: a prospective cross-sectional study

Abstract: BackgroundOtitis media is inflammation of the middle ear and tympanic membrane, which often occurs after an acute upper respiratory tract infection. It is the most common episode of infection in children and the second most important cause of hearing loss affecting 1.23 billion people, thus ranked fifth global burden of disease with a higher incidence in sub-Saharan Africa. Thus, the aim of this study was to determine the isolation rate of bacterial pathogens from pediatric patients with otitis media.Methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
17
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
9
17
1
2
Order By: Relevance
“…In the present study all bacterial isolates showed low level of resistance to ciprofloxacin (0-6.9%), and gentamicin (0-29.6%).This result is in agreement with the study by other authors in Africa where 0-33% and 0-37.5% level of resistance were reported against ciprofloxacin and gentamicin, respectively [4,19].Gram negative species of the present study also revealed low level of resistance against ceftazidime, ceftriaxone and cefotaxime. This was comparable with previous report in Ethiopia [38]. Moreover, only 16% level of resistance was reported against aztreonam in the current study.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study all bacterial isolates showed low level of resistance to ciprofloxacin (0-6.9%), and gentamicin (0-29.6%).This result is in agreement with the study by other authors in Africa where 0-33% and 0-37.5% level of resistance were reported against ciprofloxacin and gentamicin, respectively [4,19].Gram negative species of the present study also revealed low level of resistance against ceftazidime, ceftriaxone and cefotaxime. This was comparable with previous report in Ethiopia [38]. Moreover, only 16% level of resistance was reported against aztreonam in the current study.…”
Section: Plos Onesupporting
confidence: 91%
“…Moreover, only 16% level of resistance was reported against aztreonam in the current study. This was lower than a report from other part of Ethiopia [38].The low rate of resistance against 3 rd generation cephalosporins and monobactams might be due to these drugs are not commonly prescribed for the management of ear infection in the study area. Therefore, these antibiotics should be wisely used to prevent the development of resistance in Gram negative bacilli.…”
Section: Plos Onecontrasting
confidence: 64%
“…Fourteen studies were conducted on chronic suppurative otitis media [27, 31, 33, 36, 40-42, 45, 48, 50, 53, 54, 56, 58] and the rest included studies do not indicate the type of otitis media. Seven studies [30,32,35,39,44,52,57] were conducted in children whereas the rest of the studies included patients of all age groups. The average quality scores of studies ranged from 5 to 8 as per the Joanna Briggs Institute scoring scale for prevalence studies ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The most common organism isolated was Pseudomonas aeruginosa seen in 62 (33.0%), followed by Staphylococcus aureus 54 (28.7%), methicillin resistant Staphylococcus aureus 11 (5.9%), Citrobacter freundii and Proteus mirabilis 8 (4.3%), Escherichia coli 6 (3.2%) of total 171 cases similar to studies conducted by Sanjana et al, Hiremath et al, Mehta et al 13 Staphylococcus was found to be most common organisim in the study conducted by Hailegiyorgis et al and methicillin sensitive Staphylococcus aureus in Ahmad observation. 14,15 Klebsiella was found common in Malpani's study and proteus in Chirwa et al 10,16 The bacterial growth of tubotympanic disease was observed more when compared to attico antral disease with prevalence of Pseudomonas in tubotympanic and Staphylococcus in attico antral disease. The pattern of bacterial growth was observed like the study conducted by Mehta et al 13 Pseudomonas aeruginosa was susceptible to imipenem in almost all 60 cases in our study which was unique.…”
Section: Discussionmentioning
confidence: 93%